Seizure-Related Injuries among People with Epilepsy at the Outpatient Department of the University of Gondar Hospital, Northwest Ethiopia: Cross-Sectional Institutional-Based Study - Berhanu Boru Bifftu; Bewket Tadesse Tiruneh; Mengistu Mekonnen Kelkay; Nestanet Habte Bayu; Abebe Woldesellassie Tewolde; Wubet Worku Takele; Mehammed Adem Getnet; Abere Woretaw Azagew (Neurology Research International)
Background. The characteristics of epilepsy such as the episodic nature of impairment of consciousness and motor control, psychomotor comorbidity, seizure frequency, and side effects of antiepileptic drugs impact negatively on the physical safety of the patients. Physical injuries such as burn, fracture, dental loss, and hemorrhage affect the quality of patients’ life to the extent of death. Thus, the main purpose of this study was to assess the prevalence of physical injury and associated factors among people with epilepsy. Methods. The study was carried out among 409 people with epilepsy. Cross-sectional study design was utilized to enroll the selected study participants using systematic random sampling technique. Binary and multivariable logistic regression were fitted to identify associated factors using an odds ratio and 95% CI. Results. The overall estimated prevalence of seizure-related physical injury was found to be 27.9%. Of the 27.9% seizure-related physical injuries, 12.5% had abrasions, 5.9% had burns, 4.4% had dental injuries, 2.2% had fractures, and 1.5% had head injuries and dislocations, respectively. Employment, 2-3 years duration of illness, seizure frequencies, and frequencies of drug taken were factors associated with physical injury. Conclusion. More than a quarter of the study participants experienced physical injury. Designing/strengthening injury prevention strategies is suggested especially for those who had uncontrolled seizure frequency for longer period of time.